Validity Test For C-Reactive Protein and Ferritin Level in Moderate and Severe Covid-19 Patients - Kurnia, Chyntia Putriasni; Wasilah, Fajar; Lismayanti, Leni (Majalah Kedokteran Bandung, 2023)
Mild, moderate, severe, and critical COVID-19 are associated with hyperinflammation. The CRP and ferritin are acute phase proteins that marks incidence of inflammation and used as the paramaters of hyperinflammation. This study aimed to determine the validity of CRP and ferritin level examination in moderate and severe COVID-19 since the time of admission. This was a cross-sectional analytical retrospective study with on moderate and severe COVID-19 patients admitted to Dr. Hasan Sadikin General Hospital Bandung, Indonesia, during the period of March 2020 to December 2020. The CRP and ferritin levels were obtained since the beginning of admission to the fourth day since admission on patients without any history of anemia. Subjects in this study were divided into moderate and severe COVID-19 groups based on the 3rd edition of COVID-19 Prevention and Control Guideline issued by the Ministry of Health Republic of Indonesia. Each group consisted of 30 subjects. The cut-off value was 7.65 mg/dL (AUC 0.698) for CRP and 963.1 mcg/L (AUC 0.938) for ferritin. The validity of ferritin vs CRP were reflected respectively as follows:  93.3% vs 76.7% sensitivity; 80.0% vs 63.3% specificity; 82.4% vs 67.6% PPV; and 92.3% vs 73.1% NPV. The validity of ferritin was proven to be superior as it  significantly increases since day one, persisted longer and reaches its peak on  the16th day. Meanwhile, CRP increases within 6-8 hours and reaches its peak within 48 hours after inflammation, then declines soon afterwards.